Pacing strategy of single scullers during rowing world championships - Martins, A. N.; Borges, T. O.; Massa, M.; Bacurau, R. F.; Moreira, A.; Aoki, M. S. (International Journal of Applied Sports Sciences, 2023)
This study aimed to describe and compare the pacing strategy and performance of world level under 19 (U19), under 23(U23) and senior single scullers during world championship races. Data are from 8 years of Rowing World Championships A and B finals of single scull races for U19, U23 and senior age scullers. Pacing was determined for velocity, stroke rate and, distance per stroke (SD). Scullers presented a fast start strategy for all races investigated. There was no significant difference in pacing between age groups. Velocity peaked at the 100m (U19) and 150m (U23 and senior) mark. The scullers in the older age groups showed superior performance scores of the studied variables. U19, Under 23 and senior single scullers present similar pacing regardless of their age group. Performance of single sculler improve from U19, to U23 to senior for both lightweight and heavyweight classes. The results of this study may serve as a reference for athletes, coaches, and sports scientists to be implemented in training.